(untitled) - International Rice Research Institute (Manila, 1978)
There are 3 goals: 1- to exchange views on research procedures and findings; 2- To appraise the past efforts in consequences research at IRRI and 3 - To help set the goals and priorities for future work
Keywords: Rice cooperative marketing,Rice research; Varieties,Marketing